Multimodal approaches to research and pedagogy : recognition, resources, and access - Archer, Arlene; Newfield, Denise (New York : Routledge, 2014)
'This book brings together social semiotics, cultural studies, multiliteracies, and other approaches in order to theorize very different learning environments, giving visibility to the modal effect in a range of disciplines. It highlights the ideological nature of discursive practices, examines questions of access, and argues for transformation of these practices, with a constant eye on issues of social justice and equity. Contributors argue that we can harness learners' representational resources through making these resources visible, and creating less regulated spaces in the curriculum in which they can be used. Examples from primary education through to adult continuing education are used throughout the text'--
Includes bibliographical references and index.
Keywords: Modality (Linguistics).; Language and languages -- Study and teaching; Semiotics -- Social aspects; Communication -- Methodology